A Case Study of the Grey Oaks Community and Club: Creation of a High-Performance Culture Through the Innovative Use of a Data-Driven Business Plan. Issue 1 (2nd January 2016) - Fulker, Dana; Timur, Aysegul; Dew, Katherine; Butler, Jim
ABSTRACT: Grey Oaks, a premier country club and gated residential community established in Naples, Florida, developed and used a collaborative and highly feedback-driven system to build adaptive capacity and foster proactive change. Special attention has been given to the unique use and refinement of its business plan and planning process through the feedback management received from club members. This highly adaptive business plan helped Grey Oaks to endure the economic downturn that began in 2008, and the company's ability to thrive in the midst of economic instability has demonstrated the effectiveness of the plan as a model capable of sustaining the cultural and financial health of the club and community. The Grey Oaks planning model has been an innovation in its industry, and other organizations can greatly benefit by studying the implementation and utilization of this evidence-driven model.